Development and Validation of an Analytical Method to Quantitate Hydroxycitric Acid, the Key Constituent in Garcinia cambogia Extract, in Rodent Plasma and Fetus. (13th June 2022) - Mutlu, Esra; Pierfelice, Jessica; Cao, Yu; Djonabaye, Alison; Gleason, Shelly; Burback, Brian; Waidyanatha, Suramya
Abstract: Garcinia cambogia extract (GCE) is a popular botanical supplement used in weight loss products. Hydroxycitric acid (HCA) is the principal component in GCE. Due to lack of adequate toxicity data to assess the safe use of GCE, the National Toxicology Program is testing GCE in Hsd:Sprague Dawley SD rats following perinatal exposure and in adult B6C3F1/N mice. We report a validated method utilizing sample clean up with ultrafiltration followed by liquid chromatography—tandem mass spectrometry (LC-MS/MS) analysis to quantify HCA in rat plasma across the concentration range from 20 to 800 ng/mL. The method was linear (r 2 ≥ 0.99) with limits of quantitation (LOQ) and detection (LOD) equal to 20.0 and 3.9 ng/mL plasma, respectively. The accuracy (determined as the relative error, RE) and precision (determined as the relative standard deviation, RSD) using quality control standards analyzed over multiple days were ≤ ± 7.5% and ≤9.5%, respectively. The method was applied to quantify HCA in study matrices (relative error ≤ ± 23.0%; relative standard deviation ≤ 6.0) except gestational day (GD)18 fetus. The method was partially validated in GD18 fetal homogenate across the concentration range from 60 to 3000 ng/g (r 2 ≥ 0.99, relative error ≤ ± 11.9%, and relative standard deviation ≤ 5.5%; LOQ 60.0 ng/g; LOD 7.77 ng/g). Standards as high as 20, 000 ng/mL (plasma) and 502, 000 ng/g (fetus) were successfully quantified after dilution into the validated range (relative error ≤ ± 2.6%; relative standard deviation ≤ 5.2%). These results demonstrate that the method is suitable to quantify HCA in rodent matrices and may be adapted to other biological matrices.